Optimization of the business process of commercialization of developments for state educational institutions - I. A. Pestunov; G. B. Pestunova; A. A. Poguda (Открытое образование (Москва))
The purpose of the study. Today, on the basis of modern universities, favorable conditions have developed for the development of innovations, scientific developments in various directions. At the same time, financing universities from the state budget does not stimulate them to profitability and competitiveness, which may lead to a lack of motivation for the introduction of commercial approaches. Another problem is that state organizations are often characterized by complex procedures and bureaucratic clumsiness, which makes it difficult to implement commercial management methods and business approaches. The presented research is aimed at identifying the features of the business process of commercialization in public educational institutions in order to find conditions for its optimization. The topic of finding ways to optimize business processes can help budget organizations become more effective in commercializing software development for electronic computing machines and further promoting information technologies in the domestic market.The research methods were determined based on the purpose and include the analysis of scientific publications on the research topic, the method of concretization, analysis and synthesis, practical modeling, timekeeping method, employee surveys and other methods. The information base of the study was the activity of one of the structural divisions of Tomsk State University. The Competence Center for Corporate Information Systems division was established at Tomsk State University in 2019 as part of the implementation of the Digital University program to optimize the project management system based on the 1C-Bitrix24 platform. 1C-Bitrix allowed introducing digital modules of electronic document management into all systems and processes of the University into the work of Tomsk State University. At this stage of the implementation of the Digital University program, the university is taking measures to put into operation the module for the registration of business trips of employees in electronic form in the "one window" modeResults. Commercialization of software development for electronic computing machines is necessary, first of all, to make a profit and develop the developer company. If innovative developments do not turn into commercially successful products, then the company may face financing problems (including in the case of government organizations) and even financial losses. The result of the study is an optimized process of commercialization of software development for electronic computing machines for Tomsk State University during the implementation of the Digital University program in 2022. The business process was studied and an option was proposed to reduce the time of passing the stages, which in turn will lead to financial savings. The result of the study was implemented in the activities of the Competence Center for Corporate Information Systems of Tomsk State University.Conclusion. The implementation of the technology commercialization process can be led by the relevant structural units being created in universities that would be engaged in the promotion of R&D and at the same time a base for their organizational and technical support was formed. Stakeholders here are: university research and teaching staff, students, university administration, consumer companies, interested private entrepreneurs, the public and authorities. All sides of the relationship should benefit from the work of such departments of universities.